Faktor-faktor yang berhubungan dengan Status Gizi Balita - Ratifah Ratifah; Supadi Supadi; Siti Mulidah (Jurnal LINK, 2015)
The purpose of this study is to determine what factors that are relate to the children nutritional status. The research is an analytic of the factors using cross sectional research design. The subjects are 124 children that are recruited by applying simple random sampling (lottery technique). The data are collected the information in KMS and Toddler Nutrition Status Quesionnaire. We analyzed the data descriptively by applying the chi-square analysis.  The findings show that nutrition status of children related to economic stustus of parents (p=0,006), knowlege of mothers (p=0,000), education of mothers (p=0,006), exclusive breasfeeding (p=0,013), imunisation of children (p=0,045). Improvement of mothers’ knowledge of children nutrition, exclusive breasfeeding, and imunization should be given by health education. Mothers and health providers have to cooperate to complete the immunization program for the children.